Crystal structure of ethyl 2-amino-4-(3-cyanophenyl)-7,7-dimethyl-5-oxo-5,6,7,8-tetrahydro-4H-chromene-3-carboxylate, C21H22N2O4 - Yang Dao-Qiu; Li Zhen-Ming (Zeitschrift für Kristallographie - New Crystal Structures, 2018)
C21H22N2O4, monoclinic, P21/n (no. 14), a = 8.1261(14) Å, b = 11.829(2) Å, c = 20.123(4) Å, β = 98.002(3)°, V = 1915.4(6) Å3, Z = 4, Rgt(F) = 0.0394, wRref(F2) = 0.1043, T = 296(2) K.